Immigration Policies During the Pandemic In Indonesia: Economic Recovery v. Basic Rights - Susanto, Fransiska A.; Widagdo, Setyo; Haris W., Alfi (Arena Hukum, 2025)
The COVID-19 pandemic has posed a significant challenge for Indonesia and nearly all countries worldwide. Each country has implemented its own policies to address the pandemic, but these policies are not always appropriate for the public, particularly regarding reopening national borders. A similar issue has also arisen in Indonesia, where the decision to reopen borders is deemed inconsistent with the country’s societal conditions. Government policies have also impacted the state’s fulfilment of fundamental human rights. This study analyses government policies in the field of immigration during the COVID-19 pandemic, examining their social implications and proposing a policy-making model that takes human rights into account during crises. While previous research has explored the legal and economic dimensions of pandemic-era immigration policies in various countries, this study provides a distinctive focus on Indonesia’s unique regulatory inconsistencies. Using a normative research method with statutory and conceptual approaches, this study addresses the existing issues. It finds that the government’s policies have yet to fully align with the protection of human rights and that the formulation of immigration regulations during a pandemic requires a more comprehensive and well-structured approach. It underscores the importance of integrating human rights-based approaches into emergency regulations, providing valuable insights for policymakers in other jurisdictions facing similar dilemmas. By examining Indonesia’s legal framework, this research offers comparative lessons on how emerging economies can reconcile economic imperatives with legal obligations under international human rights law.